Unpacking the Image of the Female Character: The Joys of Motherhood in Perspective - Richmond Amgbo Blay; Felicia Annin (RIRAI Publisher, 2022)
This paper focuses on Buchi Emecheta’s depiction of the female character in her novel, The Joys of Motherhood. In particular, this paper examines how Emecheta directs attention at restoring the image of the “fallen” woman in the novel where the patriarchs dominate affairs. The novel achieves this aim through the narrative technique employed in the complex role of the woman figure who defiles all odds to achieve her heart desires at the end of the story. The findings reveal that Emecheta presents both positive and negative archetypal images of the African woman in the novel. It is however worthy of note that Emecheta’s negative depiction of the African woman far outweighs the positive ones. To an extent, Emecheta’s portrayal of the figure of a woman is an affront to the way a female writer ought to present the woman with exalting images rather than images of disgust.